Linguocreative nominative realia, innovations, and Russian as a foreign language - N. V. Tšuikina; E. V. Busurina (Russian State Vocational Pedagogical University, 2020)
Introduction. In recent decades, the Russian urban sociocultural environment has demonstrated the process of generation of linguocreative nominative realia (culture-bound terms) - units of language (from words to texts), created on the basis of the language game or speech stylisation to name various social and cultural phenomena. This linguistic phenomenon proves to be relevant for teaching Russian as a foreign language, specifically in light of the global trend of increasing intensity of spatial mobility of different population groups and the growing internationalisation of Russian educational system. Using linguocreative nominative units provides possibilities to implement the innovative methods in teaching foreign languages. It also allows integrating socio-cultural components in the learning process to facilitate the adaptation of international students.The aim of the current publication was to discover and describe the didactic resource of linguocreative nominative realia for teaching Russian as a foreign language.Methodology and research methods. The methodological framework of the present research was based on the provisions of competency-based approach to teaching Russian as a foreign language and the theory of critical thinking development. The introduction of ergourbanonyms (ergo urban place names) into training courses was verified by the methods of experiment, testing, interview and comparative analysis.Results and scientific novelty. In the course of the research, educational linguistic and verbal cognitive tasks were designed. The approbation was carried out during the academic year in experimental groups of foreign students, who study Russian. The authors presented didactic materials, which are based on linguocreative nominative realia. The effectiveness and perspective of the application of these materials are demonstrated. The inclusion of these teaching materials in the methodological arsenal allows solving several humanitarian tasks: for students to learn more profoundly Russian as a foreign language and to undergo a successful process of adaptation to social and living conditions of everyday environment in a target-language country; for teachers - to increase the motivation of foreign students to acquire Russian as a foreign language and to develop students' creative critical thinking. Experimental and control groups had tests in the end of the experimental period. The students of experimental groups were taught using new teaching means and tools. The training of students of control groups was organised through traditional techniques. The comparison of learning outcomes upon the probationary period showed higher level of students' communicative competency in experimental groups, and the students from the control group demonstrated considerably low level of knowledge regarding social and cultural aspects of Russian life. Summarising the results of one year's innovative experience, teaching materials and methodological guidelines were designed to organise the learning process on the basis of active learning and teaching of Russian as a foreign language.Practical significance. The didactic and methodological tools suggested in the current article can be integrated into various programmes of teaching Russian as a foreign language; the adaptation component of the materials will work within long-term programmes. The current methodological materials are ready to be implemented for classes with foreign students in any region of Russia, or they can serve as an initial sample to develop own methods and design didactic materials.